What makes a strong organic electron donor (or acceptor)? - Eberle, Benjamin; Hübner, Olaf; Ziesak, Alexandra Sabrina; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2015)
Organic electron donors are of importance for a number of applications. However, the factors that are essential for a directed design of compounds with desired reduction power are not clear. Here, we analyze these factors in detail. The intrinsic reduction power, which neglects the environment, has to be separated from extrinsic (e.g., solvent) effects. This power could be quantified by the gas-phase ionization energy. The experimentally obtained redox potentials in solution and the calculated ionization energies in a solvent (modeled with the conductor-like screening model (COSMO)) include both intrinsic and extrinsic factors. An increase in the conjugated π-system of organic electron donors leads to an increase in the intrinsic reduction power, but also decreases the solvent stabilization. Hence, intrinsic and extrinsic effects compete against each other; generally the extrinsic effects dominate. We suggest a simple relationship between the redox potential in solution and the gas-phase ionization energy and the volume of an organic electron donor. We finally arrive at formulas that allow for an estimate of the (gas-phase) ionization energy of an electron donor or the (gas-phase) electron affinity of an electron acceptor from the measured redox potentials in solution. The formulas could be used for neutral organic molecules with no or only small static dipole moment and relatively uniform charge distribution after oxidation/reduction.
Gesehen am 06.07.2020